2015
DOI: 10.1242/jcs.173518
|View full text |Cite
|
Sign up to set email alerts
|

Carcinoma cells induce lumen filling and EMT in epithelial cells by soluble E-cadherin-mediated activation of EGFR

Abstract: In epithelial cancers, carcinoma cells coexist with normal cells. Although it is known that the tumor microenvironment (TME) plays a pivotal role in cancer progression, it is not completely understood how the tumor influences adjacent normal epithelial cells. In this study, a three-dimensional co-culture system comprising non-transformed epithelial cells (MDCK) and transformed carcinoma cells (MSV-MDCK) was used to demonstrate that carcinoma cells sequentially induce preneoplastic lumen filling and epithelial-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 63 publications
1
27
0
Order By: Relevance
“…More interestingly, this feedback loop also participates in the oncogenic transformation of normal epithelial cells: MMPs derived from cancer cells cleave the extracellular domain of E‐cad between normal epithelial cells to release sE‐cad to bind to the EGFRs located at the surface of normal epithelial cells. The EGFR signaling pathway is thus activated to promote the malignant transformation of these cells …”
Section: Se‐cad and Cancer Progressionmentioning
confidence: 99%
“…More interestingly, this feedback loop also participates in the oncogenic transformation of normal epithelial cells: MMPs derived from cancer cells cleave the extracellular domain of E‐cad between normal epithelial cells to release sE‐cad to bind to the EGFRs located at the surface of normal epithelial cells. The EGFR signaling pathway is thus activated to promote the malignant transformation of these cells …”
Section: Se‐cad and Cancer Progressionmentioning
confidence: 99%
“…Like AQP5, the lumens of the cysts formed by AQP5 S156A were also filled with cells, but to a lesser extent than the AQP5 cysts, indicating that serine 156, probably through Ras-signaling activation, contributes to cell migration into cyst lumens. Presence of cells within the cyst lumens has been described in cases of perturbed cell polarity or dysregulation of major signaling pathways, which are features often displayed by cancer cells (7,12,46). Together, these data show that AQP5 expression causes lower cell adhesiveness and promotes cell detachment and dissemination from the migrating sheet or migration into the cyst lumens.…”
Section: Aqp5 Expression Decreases Plasma Membrane-associated Junctiomentioning
confidence: 62%
“…However, the mechanisms of luminal filling initiation are poorly understood. Recent studies have reported that carcinoma cells directly contact normal epithelial cells through filopodia-like projections in the 3D co-culture system, or they secrete MMP-9 that cleaves E-cadherin disrupting the luminal architecture [28], or alternatively they use exosomes to induce oncogenic transformation of adjacent normal epithelial cells [29]. Our results were consistent with previous reports, and we went a step further and compared the properties of C2 and C3 cancer cells and found that the transmitted cancer cells (C2 cells) were more malignant than the original cancer cells (C3 cells), which could explain how cancer heterogeneity is formed.…”
Section: Discussionmentioning
confidence: 99%